The Position of Civil Servant Investigators in the Disclosure of Money Laundering Crimes after the Constitutional Court's Decision Number 15/PUU-XIX/2021 - Jetter Wilson Salamony (PT Publikasiku Academic Solution, 2024)
The role of Civil Servant Investigators (PPNS) in Indonesia has evolved, particularly following the Constitutional Court Decision Number 15/PUU-XIX/2021, which expanded their authority in money laundering investigations. This study aims to analyze the impact of this decision on the position and authority of PPNS within the integrated criminal justice system. Using a normative legal approach, the research employs primary data from the Constitutional Court s ruling and secondary data from legal literature and relevant media sources. The findings indicate that the Constitutional Court s decision not only enhances the investigative powers of PPNS but also aligns them with other law enforcement agencies, such as the National Police and the Corruption Eradication Commission. Despite this expansion, the study highlights ongoing challenges, particularly the dependency of PPNS on police investigators during the prosecution process. The relationship between PPNS and other law enforcement officials is crucial for effective law enforcement and the prevention of money laundering crimes. The study concludes that the broadened authority of PPNS should be viewed as a collaborative effort rather than competition, emphasizing the importance of coordination among agencies to strengthen law enforcement efforts in Indonesia.